2020
DOI: 10.4236/oalib.1106144
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effects of Atmospheric Pressure Air DBD Plasma on Physio-Chemical and Microbial Parameters of Groundwater

Abstract: Cold atmospheric pressure plasma generated at atmospheric air produces high energetic electrons, ions, UV radiations, reactive oxygen, and nitrogen species (RONS) which has a wide range of applications in biomedicine, agriculture, textiles, water treatment, etc. Recently, many researches have been carried out on ozonation through DBD (Dielectric barrier discharge) plasma in water treatment. However, direct plasma treatment on water hasn't been extensively studied yet. In this study, we examined the change in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Consistent with our study, several studies have reported a decrease in the pH of solutions after cold plasma treatment. A gradual declination in the pH of a groundwater sample was reported over time when treated with a dielectric barrier discharge plasma system [34]. Similarly, a decrease in the pH of plasma-treated water with air as the influent gas was attributed to the effects of nitric and nitrate acids produced as a result of the reaction between H 2 O molecules and NOx species [37].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Consistent with our study, several studies have reported a decrease in the pH of solutions after cold plasma treatment. A gradual declination in the pH of a groundwater sample was reported over time when treated with a dielectric barrier discharge plasma system [34]. Similarly, a decrease in the pH of plasma-treated water with air as the influent gas was attributed to the effects of nitric and nitrate acids produced as a result of the reaction between H 2 O molecules and NOx species [37].…”
Section: Discussionmentioning
confidence: 96%
“…Cold plasma removed 98.9% of Fe at a low Fe concentration (3.76 mg•L −1 ), and 97.8% of Fe at a 9.09 mg•L −1 concentration. One experiment [34] studied the change in physical, chemical, and biological parameters of groundwater by means of direct dielectric discharge barrier plasma activation. There was a significant reduction in the concentration of heavy metals such as chromium, manganese, cadmium, iron, lead, and zinc after cold plasma treatment.…”
Section: Discussionmentioning
confidence: 99%
“…8,59,60 Electrical conductivity (EC) usually identifies active ions present in a liquid and measures the liquid's ability to transport an electrical current. 19,24,61 There was a significant increment of EC in PAW samples as plasma activation time increased, reaching 58.6 ± 1.60 µS/cm at 10 min, pointing out the generation of active ions in PAW.…”
Section: E Physical and Chemical Specificationsmentioning
confidence: 90%
“…It has potentially a wide range of applications including environmental and biological fields such as food sterilization, cancer cell treatment, materials processing, and wastewater treatment. In package decontamination of foods, using cold plasma has advanced this technology as a single process for fresh foods decontamination and shelf-life extension [8,9]. e cold plasma treatment is effective for both underground water as well as surface drinking water to enhance their quality.…”
Section: Introductionmentioning
confidence: 99%